The cost of aiming for the best answers: Inconsistent perception - Smeets, Jeroen B. J.; Brenner, Eli (Frontiers in Integrative Neuroscience, 2023)
The laws of physics and mathematics describe the world we live in as internally consistent. As these rules provide a very effective description, and our interaction with the world is also very effective, it seems self-evident that our perception follows these laws. As a result, when trying to explain imperfections in perception, we tend to impose consistency and introduce concepts such as deformations of visual space. In this review, we provide numerous examples that show that in many situations we perceive related attributes to have inconsistent values. We discuss how our tendency to assume consistency leads to erroneous conclusions on how we process sensory information. We propose that perception is not about creating a consistent internal representation of the outside world, but about answering specific questions about the outside world. As the information used to answer a question is specific for that question, this naturally leads to inconsistencies in perception and to an apparent dissociation between some perceptual judgments and related actions.